Penguatan Hukum Tentang Perjanjian Kredit Pada Koperasi Bagi Masyarakat - Haliwela, Nancy Silvana; Lakburlawal, Mahrita Aprilya (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: Credit to cooperatives has become a choice for the community, due to easy credit requirements and a faster credit disbursement process. Credit is extended by the cooperative to the community (debtor), through a credit agreement made between the cooperative and the community (debtor). A credit agreement made legally, legally binding on the parties. However, it is undeniable that many credit problems lead to bad credit, due to the lack of public legal knowledge about credit agreements.Purposes of Devotion: Strengthening the law regarding credit agreements for the community is the focus of study in community service activities, which is important to convey to the community, in order to provide legal understanding and education regarding credit agreements for the community. Method of Devotion: Strengthening the law is carried out through legal counseling using the panel discussion method, where the speaker first delivers the material, followed by a questions and answers session between the community and the presenter.Results of the Devotion: Communities in Toisapu Hamlet, Hutumuri Village, Leitimur Selatan District, Ambon City, have made many credit agreements with cooperatives for capital for business activities and also for the consumptive needs of the community. As a result of the lack of legal knowledge about credit agreements, it has resulted in various legal issues between the community (debtor) and the cooperative. People (debtors) are entangled with credit, credit arrears occur and bad credit occurs. This raises a dispute between the community (debtor) and the Cooperative. The community (debtor) does not understand the credit agreement, resulting in credit not guaranteeing an increase in community business activities (debtors) instead it becomes a debt burden for the community (debtors).